Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1590/s1519-566x2008000300013
|View full text |Cite
|
Sign up to set email alerts
|

Perspectivas para a criação massal de Iphiseiodes zuluagai Denmark & Muma (Acari: Phytoseiidae)

Abstract: -Iphiseiodes zuluagai Denmark & Muma is an important predator of Brevipalpus phoenicis (Geijskes) on citrus in Brazil. The suitability of Tyrophagus putrescentiae (Schrank) as a food source of I. zuluagai in laboratory rearing was investigated at 25.5 ± 0.5ºC, 88 ± 7% RU and photophase of 12h. Initially, levels of oviposition of the predator fed on eggs were evaluated, as well as the dead or live post-embryonic stages of T. putrescentiae, in a period of 10 days. The daily oviposition rate was 1.3 egg per femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 21 publications
(26 reference statements)
0
3
0
1
Order By: Relevance
“…The astigmatids evaluated were not adequate for the mass production of I. zuluagai, nor did they support even temporary survivorship, as indicted by low values for intrinsic rate of increase, oviposition and survivorship. Albuquerque and Moraes (2008) reported even lower oviposition by this predator on post-embryonic stages of T. putrescentiae. Still, the predator did feed on D. pteronyssinus and S. nesbitti, and about half the immatures reached adulthood.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The astigmatids evaluated were not adequate for the mass production of I. zuluagai, nor did they support even temporary survivorship, as indicted by low values for intrinsic rate of increase, oviposition and survivorship. Albuquerque and Moraes (2008) reported even lower oviposition by this predator on post-embryonic stages of T. putrescentiae. Still, the predator did feed on D. pteronyssinus and S. nesbitti, and about half the immatures reached adulthood.…”
Section: Discussionmentioning
confidence: 87%
“…Albuquerque and Moraes (2008) observed better performance of I. zuluagai when T. putrescentiae eggs were provided compared to all life stages combined and obtained an r m value of 0.11 females per female per day. Prey foods may also influence predator performance: Sarwar et al (2010) obtained faster development, higher fecundity and greater longevity of Neoseiulus pseudolongispinosus (Xin, Liang and Ke) when prey (T. putrescentiae) were reared on wheat flour compared to corn or soybean flour.…”
Section: Neoseiulus Barkerimentioning
confidence: 80%
“…The mite species considered in this study are commonly found in citrus orchards throughout the country (Bittencourt and da Cruz, 1988;Sato et al, 1994;Reis et al, 2000;Albuquerque and Moraes, 2008;Silva et al, 2013;Noronha, 2013). Regarding the distribution of plants providing the best results, E. guineensis is mainly grown in northern Brazil and in the Bahia State (northeast), producing abundant pollen (Cunha et al 2007).…”
Section: Scientific Namementioning
confidence: 99%
“…Além de contribuir para o aumento na densidade populacional de artrópodes-pragas, os inseticidas também podem reduzir ou alterar os parâmetros biológicos e demográficos dos inimigos naturais das pragas presentes nos agroecossistemas, reduzindo o potencial de ação desses agentes biológicos no controle natural de artrópodes-praga. Entre os inimigos naturais, o ácaro predador Iphiseiodes zuluagai Denmark & Muma (Acari: Phytoseiidae) é uma das espécies mais abundantes em plantas em cítricas MORAES, 2002;ALBUQUERQUE;MORAES, 2008). Esse predador possui ampla distribuição no território nacional (REIS et al, 2000;MORAES, 2002;MORAES et al, 2004) e está associado principalmente ao ácaro da leprose Brevipalpus phoenicis (Geijskes) (Acari:…”
Section: Introductionunclassified